Metazoan parasites of Plagioscion squamosissimus, an invasive species in the Tietê River, São Paulo, Brazil - Lapera, Ivan Moura [UNESP]; Silva, Ana Carolina da [UNESP]; Canônico, Bruno Marreto [UNESP]; Perezin, Gabriela de Farias [UNESP]; Tebaldi, José Hairton [UNESP]; Pala, Gabriela [UNESP]; Manrique, Wilson Gómez; Hoppe, Estevam Guilherme Lux [UNESP] (FapUNIFESP (SciELO), 2017)
This study focused on the characterization and analysis of communities and infra-communities of metazoan parasites of Plagioscion squamosissimus caught in Promissão Reservoir in the Tietê River in Borborema (21°39'58“S, 49°8'49“W), state of São Paulo, Brazil. Fifty adult specimens caught by professional fishermen in March 2015 were necropsied. The fish presented an average standard length of 25.2 ± 2.2 cm and average weight of 328.82 ± 89.03 g. A total of 5,227 specimens of metazoan parasites were collected: 2,880 (55.1%) adult Diplectanum piscinarius (Monogenoidea: Diplectanidae) and 2,347 (44.9%) Austrodiplostomum compactum metacercariae (Digenea, Diplostomidae), both with 100% prevalence and mean abundance of 57.6 and 46.9, respectively. Parasite diversity was low (species richness = 2), with a Simpson index (D) equal to 0.505, and low values of Brillouin (HB = 0.687) and Margalef diversity (I = 0.117) indices. Berger-Parker’s index of dominance (p = 0.551) indicated a slight dominance of the monogenean parasite D. piscinarius. There was a positive correlation, assessed by Pearson coefficient between parasite abundance of D. piscinarius and standard length (r = 0.43) and weight (r = 0.51) of hosts.
Parasitas metazoários de Plagioscion squamosissimus, uma espécie invasora no Rio Tietê, São Paulo
Keywords: Austrodiplostomum compactum; Diplectanum piscinarius; Freshwater fish; Parasite ecology; South american silver croaker